Application of the Problem Based Learning Model to Improve the Cognitive Learning Outcomes of Grade V Students of SDN Alasrajah 2 in Pancasila Education Subjects - Sofiatul Adawiyah Fatha; Ashish Katare; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model in improving the cognitive learning outcomes of fifth-grade students at SDN Alasrajah 2 in the subject of Pancasila Education. This classroom action research was conducted in two cycles. In the pre-cycle stage, only 40% of students met the minimum mastery criteria. After applying the PBL model in the first cycle, the percentage increased to 80%, and further improved to 92% in the second cycle. These results demonstrate that the PBL model effectively enhances students’ cognitive performance, encourages active participation, and fosters critical thinking skills through problem-solving activities related to real-life issues and Pancasila values. It can be concluded that PBL is a highly effective learning model for improving student outcomes in civic education at the elementary level.